Capital Taxation and Imperfect Competition: ACE vs. CBIT - Dirk Schindler; Kurt Brekke; Armando Pires; Guttorm Schjelderup (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper sets up an imperfect-competition model of a small open economy, and undertakes a welfare comparison of the Corporate Business Income Tax (CBIT) and the Allowance for Corporate Equity tax (ACE). A main result is that a small open economy should levy a positive source tax on capital in a market with free firm entry. Our analysis also shows that the well known neutrality property of the ACE tax is no longer true when firms are mobile and can enter the market. Which tax system is better from a welfare point of view, CBIT or ACE, is shown to depend on assumptions about production technology and entry.
Keywords: H25; D43; H32; 330